Dealing with Vulnerability During a Pandemic: Pregnant Women's Perspectives - Yosef Andrian Beo; Retno Lestari; Asti Melani Astari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The coronavirus affects the psychological condition of mothers during pregnancy; therefore, they are vulnerable to experience anxiety, stress, and depression during the pandemic. This phenomenological study aims to explore the experiences of pregnant women in dealing with pandemic situations. This qualitative study used an interpretive phenomenological approach and in-depth interviews with 10 pregnant women as participants. The data were transcribed and analyzed using an interpretative phenomenological approach. The results led to 9 main themes, include: (1) considering COVID-19 as scary, (2) anxiety due to increased risk of contracting the virus during pregnancy, (3) increased stress during pregnancy, (4) being constrained due to limited activities, (5) couples becoming the main support, (6) the support of people around creates positive feelings, (7) becomes more disciplined in implementing health protocols, (8) more active in using social media, and (9) familiarize with the changing situation of the pandemic. It can be concluded that pregnant women develop new habits during pandemics, such as seeking support from partners and others, adhering to health protocols, being active on social media, and adapting to the pandemic situation.  Virus corona mempengaruhi kondisi psikologis ibu selama kehamilan sehingga mereka sangat rentan mengalami kecemasan, stres, dan depresi selama masa pandemi. Studi fenomenologi ini bertujuan untuk menggali pengalaman ibu hamil dalam menghadapi situasi pandemi. Penelitian kualitatif ini menggunakan pendekatan interpretif fenomenologis dan wawancara mendalam pada 10 ibu hamil sebagai partisipan. Data ditranskripsi dan dianalisis menggunakan pendekatan fenomenologi interpretatif. Hasil penelitian menghasilkan 9 tema utama, antara lain: (1) menganggap COVID-19 sebagai hal yang menakutkan, (2) kecemasan karena meningkatnya risiko tertular virus selama kehamilan, (3) meningkatnya stres selama kehamilan, (4) terkendala karena aktivitas yang terbatas, (5) pasangan. menjadi pendukung utama, (6) dukungan orang sekitar menciptakan perasaan positif, (7) menjadi lebih disiplin dalam menerapkan protokol kesehatan, (8) lebih aktif menggunakan media sosial, dan (9) membiasakan diri dengan perubahan situasi pandemi. Dapat disimpulkan bahwa ibu hamil mengembangkan kebiasaan baru selama pandemi, seperti mencari dukungan dari pasangan dan orang lain, mematuhi protokol kesehatan, aktif di media sosial, dan beradaptasi dengan situasi pandemi.